Ultraviolet Shielding Performance of Coconut Coir as a Filler in Low-Density Polyethylene (LDPE) Plastic Mulch - Andreansyah, Ilham; Mentari, Puji Rizana Ayu; Rahman, Herliati; Syamani, Firda Aulya (Masyarakat Peneliti Kayu Indonesia, 2023)
Plastic mulch is a layer of material applied to the soil surface to maintain moisture retention in the soil by preventing evaporation, reduce weed growth by blocking sunlight from reaching underlying weeds, and optimize fertilizer use by minimizing nutrient loss to the environment. However, the degradation of low-density polyethylene (LDPE), a thermoplastic commonly used for mulching, into microplastics due to exposure to UV radiation. This research explored the potential of coconut coir, a natural fiber with a high lignin content ranging from 30 to 46%, as a UV protective agent. The objective was to develop biodegradable plastic-based mulch composites that have better resistance to UV exposure by incorporating coir as a filler material in LDPE-based composites. Different ratios of coconut fiber were used (10%, 20%, 30%, and 40%), and Maleic anhydride grafted polyethylene (PE-g-MAH) was used as a binder at 2% of total weight mixed with LDPE in a rheomixer (80 rpm, 120°C for 10 min). The resulting plastic mulch bio-composites were evaluated for thermal, mechanical, UV resistance, and biodegradability properties. The results showed that the higher addition of coconut coir resulted in a decrease in the thermal and mechanical characteristics of the composite. However, the addition of higher coconut coir in the composite at 40% can provide an increase in the composite's resistance to ultraviolet light exposure, and the properties are easily degraded by the environment (biodegradable).